Quality of life assessment in patients after permanent pacemaker implantation at Haji Adam Malik Hospital Medan - Khairunnisah, Dina; Ali Nafiah Nasution; Refli Hasan; Nizam Zikri Akbar; Anggia Chairuddin Lubis; Abdul Halim Raynaldo (Universitas Brawijaya, 2025)
Background: PPM implantation is used to send electrical impulses to the heart muscle to correct heart rhythm disturbances also known as cardiac arrythmia. Assessing the patient's quality of life after a PPM implantation is crucial for predicting the therapy's effectiveness and success. Objectives: This study aims to assess the quality of life of patients following pacemaker implantation by using the SF-36 questionnaire. Methods: A cross-sectional study conducted from January 2021 to July 2023 on 60 outpatients with a minimum duration of PPM implantation of 6 months in the cardiology department of H. Adam Malik Hospital Medan. Patient’s quality of life was assessed based on the SF-36 questionnaire. Subjects then were grouped based on age, gender, PPM duration and location, as well as other echocardiographic parameters that may affect patient’s quality of life after PPM implantation. Results: There were 60 patients included in this study. Majority of patients were male (56.7%) with an average age of 67.98 ± 10.95 years old and most patients had comorbidities (81.7%). The majority of patients (93.3%) had a single-chamber permanent pacemaker implanted, with 68.3% of these devices’ ventricular leads positioned in the non-apical segment of the heart. After assessing the quality of life, we found there’s a relationship between age, gender, and PPM lead locations with nearly all SF-36 domains (p<0.05). Additionally, there was a significant association between comorbidities and SF-36 scores, including physical function, physical limitations, and emotional limitations (p<0.05). There was a significant association between ejection fraction and SF-36 scores, including physical function, role limitations due to physical health problems, vitality, social function, bodily pain and general health. However, no relationship was found between IMT and PPM implantation duration with SF-36 scores (p>0.05). Conclusion: We identified a relationship between age, gender, comorbidities, PPM lead location, and ventricular ejection fraction with the quality of life of patients following PPM implantation